Long non-coding RNAs and messenger RNA isoforms associated with muscle fatty acid profile in Nellore animals - Salatta, Bruna Salatta [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
In recent decades, considerable attention has been paid to the increase in beneficial fatty acids (FA) present in foods of animal origin. Traits of economic importance in beef cattle, as well as the meat fatty acid profile, are polygenic in nature and are influenced by genetic and environmental factors. In this sense, the RNA sequencing (RNA-Seq) is a technique employed to examine the expression of functional candidate genes, allowing the identification of significant molecular mechanisms that lead to variations in pathways responsible for distinct tissue phenotypes. Therefore, the objective was to study the transcriptome of Nellore cattle muscle, aiming to identify differentially expressed long non-coding RNAs (lncRNAs) and mRNA isoforms associated with FAs, through RNA-Seq. For this purpose, 48 animals were sequenced and phenotyped to seven individual FAs: myristic, palmitic, stearic, oleic, linoleic, conjugated linoleic, alpha-linolenic; and seven FA groups: sum of saturated FAs, monounsaturated FAs, polyunsaturated FAs, ω3, ω6, PUFA/SFA ratio, and ω6/ω3 ratio. K-means analysis was employed to cluster 48 animals into three groups based on their FA patterns. Cluster C1 exhibited significantly higher proportions (p ≤ 0.05) of polyunsaturated fatty acids (PUFA), including ω3, ω6, linoleic, and α-linolenic acids compared with C2 and C3. The proportion of monounsaturated fatty acids (MUFA) conjugated linoleic acid, and oleic acid in C2 and C3 was significantly (p ≤ 0.05) higher compared to C1, while C3 showed significantly higher proportions (p ≤ 0.05) of saturated fatty acids (SFA), myristic, palmitic, and stearic acids in comparison to the other clusters. For transcriptome analysis, a pairwise comparison experiment between two groups (C1 vs. C2, C1 vs. C3, and C2 vs. C3) was conducted. The results are presented in Chapters 2 and 3. In Chapter 2, a total of 265 long non-coding RNA (lncRNA) transcripts were differentially expressed (p-value < 0.01), being that 75, 113, and 78 identified in the C1 vs. C2, C1 vs. C3, and C2 vs. C3 comparisons, respectively. These lncRNAs were associated with genes belonging to the interferon, interleukin, G protein-coupled receptor, calponin, and apoptotic Bcl-2 families. Functional enrichment analysis revealed that many Gene Ontology (GO) terms were associated with the immune system in genetic profiles with higher saturated fatty acid (SFA) content (e.g, SERPINE1). In Chapter 3, a total of 65, 26, and 30 mRNA isoforms were differentially expressed (p-value < 0.01) in the C1 vs. C2, C1 vs. C3, and C2 vs. C3 comparisons, respectively. Additionally, differentially expressed isoforms, such as C7-203, ADD1-204, OXT-201 and RBM3-202, were linked to genes affecting polyunsaturated fatty acid content in the C1 vs. C2 comparions, while other mRNA isoforms important for saturated fatty acid content, such as EGR1-201, FOSB_mRNA1, and SERPINE1_mRNA1, were identified in the C1 vs. C2 comparison. Moreover, functional enrichment analysis highlighted various terms associated with fatty acid metabolism, as well as terms related to oxidoreductase activity, lipid transport, and immune response. This thesis provided insights into potential lncRNA and mRNA isoform candidates associated with FA in beef cattle, contributing to a better theoretical understanding of biological processes associated with this feature. This information may contribute to future research focused into identification of genetic markers to be applied in genetic selection of animals with better FA profiles.

Nas últimas décadas, considerável atenção tem sido dada ao aumento de ácidos graxos (AG) benéficos presentes em alimentos de origem animal. Características de importância econômica na pecuária de corte, assim como o perfil de ácidos graxos da carne, são de natureza poligênica e influenciadas por fatores genéticos e ambientais. Nesse sentido, sequenciamento do RNA (RNA-Seq) é uma das abordagens utilizadas para identificar transcritos correspondentes a genes candidatos que provocam variações em vias metabólicas, resultando em diferentes fenótipos. Portanto, o objetivo foi estudar o transcriptoma do músculo de bovinos da raça Nelore, com o propósito de identificar RNAs longos não codificantes (lncRNAs) e isoformas de mRNAs diferencialmente expressas associados à AG, por meio do RNA-Seq. Para tanto, 48 animais foram sequenciados e fenotipados para sete indivíduais: mirístico, palmítico, esteárico, oleico, linoleico, linoleico conjugado, alfa-linolênico; e sete grupos: soma de AG saturados, monoinsaturados, poliinsaturados, ω3, ω6, razão PUFA/SFA e razão ω6/ω3). A análise K-means foi usada para agrupar os 48 animais em três clusters com base em seus padrões de AG. O cluster C1 apresentou proporções significativamente (p ≤ 0,05) mais altas de AG poliinsaturado, incluindo ω3, ω6, linoléico e α-linolênico. A proporção de AG monoinsaturados, linoleico conjugado e oleico no C2 e C3 foi significativamente (p ≤ 0,05) maior em relação ao C1, enquanto o C3 teve proporções significativamente (p ≤ 0,05) maiores para AG saturado, mirístico, palmítico e esteárico em relação aos demais clusters. Para a análise do transcriptoma o experimento de comparação de dois grupos (C1 vs. C2, C1 vs. C3 e C2 vs. C3) foi usada. Os resultados foram apresentados nos capítulos 2 e 3. No capítulo 2, um total de 265 transcritos de lncRNAs foram diferencialmente expressos (p-value < 0,01), dos quais 75, 113 e 78 foram identificados entre as comparações C1 vs. C2, C1 vs. C3 e C2 vs. C3, respectivamente. Os lncRNAs foram associados a genes pertencentes a família de interferon, interleucina, receptores acoplados à proteína G, calponina e apoptóticas Bcl-2. A análise de enriquecimento funcional mostrou que muitos dos termos da ontologia genética (GO) estavam associados com o sistema imune para comparação (C2 vs. C3), que são grupos com maior conteúdo de SFA (p. ex. IFN-TAU and IFNAG). No capítulo 3, foram identificados 65, 26 e 30 isoformas de mRNA (p-value < 0.01) diferencialmente expressas entre as comparações C1 vs. C2, C1 vs. C3 e C2 vs. C3, respectivamente. As isoformas, C7-203, ADD1-204, OXT-201 e RBM3-202, foram diferencialmente expressa in C1 em ralação a C2 e são 17 relacionadas a genes que afetam o conteúdo de AG poliinsaturado. Enquanto na comparação C1 vs. C2, foram encontradas isoformas de mRNA relacionadas ao conteúdo de AG saturado como, por exemplo, EGR1-201, FOSB_mRNA1, e SERPINE1_mRNA1. Além disso, a análise do enriquecimento funcional aponta diversos termos associados ao metabolismo de ácidos graxos, oxirredutase, transporte lipídico e resposta imune. Esta Tese forneceu insights sobre potenciais candidatos a isoformas de lncRNA e mRNA associados à AG em bovinos de corte, contribuindo para uma melhor compreensão teórica dos processos biológicos associados a esta característica. Estas informações poderão contribuir para futuras pesquisas focadas na identificação de marcadores genéticos a serem aplicados na seleção genética de animais com melhores perfis de AG.
RNAs longos não-codificantes e isoformas de RNA mensageiro associadas ao perfil de ácidos graxos musculares em animais Nelore
Keywords: livestock; Fatty acids; Bovine Nellore; LincRNA